Sobre su cadáver: diplomacia entre México y Estados Unidos, y la ejecución de Maximiliano de Habsburgo en México, 19 de junio de 1867 - Sweeney, Lean (El Colegio de México, A.C., 2019)
On June 19, 1867, Archduke Maximilian of Habsburg was executed by a firing squad at Cerro de las Campanas, Querétaro on the order of Mexican President Benito Juárez. Rather than representing one of the clearest episodes of the 19th Century of nationalist triumph over imperialism and dynastic domination, this event has been commonly remembered as the somber curtain of the dramatic personal and political life of Maximilian. This article argues that, despite his intentions, Juárez did not consolidate his legitimacy as leader of Mexico through the execution of Maximilian, but rather in spite of it. Rather than showing the authority and justice of the triumphant republicans, the execution increased the irrelevance of Maximilian and U.S. support in Mexico’s national history. In this context, the execution, body and memory of Maximilian gave rise to an alternate narrative of the triumph of Mexican nationalism. In this narrative. Maximilian becomes a symbol of the tragedy of war and the immortality of the royal legacy, an image that ignored the propagandistic intentions of Juárez and the “Radical Republicans” in the United States. This article is based on the records of the trial of Maximilian of Habsburg, Juárez’s defense of the execution, the diplomatic correspondence within the United States and between the United States and Mexico, the records of the U.S. Congress and the popular responses in photography and the press. This article offers a unique vision of U.S.-Mexico relations with implications for the studies of the empire in the 19th Century and the construction of the nation in general.